Manajemen Sumber Daya Manusia dalam Perspektif Filsafat Humanisme - Yhonanda Harsono (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2025)
Human Resource Management (HRM) is a strategic organizational function focused on managing people as the primary drivers of organizational activity. However, modern HRM practices are often dominated by technocratic and economistic approaches that tend to reduce humans to mere means of production. This article aims to examine HRM from the perspective of humanist philosophy as an alternative approach that positions humans as dignified subjects with the potential for development. This research uses qualitative methods with a library study approach to HRM literature and humanist philosophy. The results indicate that humanist philosophy provides an ethical and philosophical foundation for HRM practices oriented toward respect for human dignity, justice, and the development of individual potential. The integration of humanist values ​​into HRM contributes to improved employee well-being and organizational sustainability.